Summary of Variables Associated with Application of Plant Protection Products in Peanut. Issue 1 (18th October 2018) - Jordan, David L.; Hare, Andrew T.; Roberson, Gary T.; Shew, Barbara B.; Brandenburg, Rick L.; Anco, Dan; Balota, Maria; Mehl, Hillary; Taylor, Sally
Abstract : Core Ideas: Peanut acreage was positively correlated with tank size, boom width, and ground speed. Peanut acreage was not correlated with peanut yield, spray volume, and spray pressure. Co‐applying three or more products in the same tank was common among growers. Flat‐fan nozzles were the most commonly used spray nozzles among peanut growers. Growers spend approximately 18% of their time applying crop protection products.